Analisis Pengaruh Laba Bersih, Total Arus Kas, Firm Size dan Price To Book Value (PBV) terhadap Return Saham (Studi Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang terdaftar di BEI Tahun 2013-2015) - Lusiana Dwi Kartika; Riri Purwacasila (Faculty of Economics and Business, University of Pancasakti Tegal, 2016)
The purpose of this study is 1) to find out the effect of net income, total cash flow, firm size and price to book value (PBV) on stock returns. 2) to determine the effect of net income on stock returns. 3) to determine the effect of the total cash flow on stock returns. 4). To determine the effect of firm size on stock returns. 5). to determine the effect of price to book value (PBV) on stock returns. The hypothesis in this study is that it is assumed that Net Profit, Total Cash Flow, Company Size, Price to Book Value (PBV) together have a positive effect on stock returns. The method selection is descriptive quantitative. Data Collection Techniques conduct library studies. Techniques of data analysis using classical assumption test, multiple linear regression analysis, hypothesis testing. Based on the results of the study, the first hypothesis is acceptable, it is proven from the results of testing the significant test simultaneous parameters (F statistical test) obtained probability of a sig value of 0.002 which is smaller than the value of a which is equal to 0.05. Based on the results of the study, the second hypothesis is acceptable, it is evidenced from the results of testing the significant test of individual parameters (statistical test t) net income on stock returns obtained probability of sig value of 0.046 which is smaller than a value of 0.05. Based on the results of the study, the third hypothesis is unacceptable, it is proven from the results of testing the significant test of individual parameters (statistical test t) the total cash flow to stock returns obtained probability of sig value of 0.271 which is greater than a value of 0.05. Based on the results of the study, the fourth hypothesis is unacceptable, it is evidenced from the results of testing the significant test of individual parameters (statistical test t) firm size of stock returns obtained probability of sig value of 0.708 which is greater than a value of 0.05. Based on the results of the study, the fifth hypothesis can be accepted, it is proven from the results of testing the significant test individual parameters (statistical test t) price to book value on stock returns obtained probability of sig value of 0.023 which is smaller than a value of 0.05.